Impact of dosing frequency (once daily or twice daily) on patient adherence to oral targeted therapies for hematologic malignancies: a retrospective cohort study among managed care enrollees. (December 2019) - Patel, Krish; Sudhir, Vinjamuri S; Kabadi, Shaum; Huang, Joanna C; Porwal, Sanchita; Thakkar, Kushan; Pagel, John M
Purpose: Existing studies evaluating patient adherence to oral targeted therapies such as tyrosine kinase inhibitors focus on small populations with single malignancies. This study evaluated patterns of use of oral agents in a larger population across multiple hematologic malignancies. Methods: Adult patients diagnosed with a hematologic malignancy and prescribed oral targeted therapy between 2011 and 2016 ( N = 18, 976) were identified from the MarketScan Commercial Claims and Encounters, and Medicare Supplemental databases. Eligible patients were enrolled in monthly prescription plans 6 months before and 12 months after the index date (date of first prescription claim; n = 2442). Multivariable logistic regressions were used to determine predictors of adherence using the medication possession ratio (MPR) and persistence through prescription refill gaps. Results: The overall median adherence was 0.9 (MPR ≥ 80%) and was comparable between once-daily (QD) and twice-daily (BID) groups. Overall, 59% of patients were persistent at 12 months. Patients on QD and BID products did not have any significant differences in adherence (fixed-interval MPR, odds ratio 0.94; 95% confidence interval (CI), 0.75–1.18) or persistence (odds ratio 0.93; 95% CI, 0.75–1.17) 12 months from index. Significant predictors of adherence and persistence included patient age, total inpatient admissions, number of adverse events, and total hospital visits. Conclusion: Patient-specific clinical factors, rather than regimen-specific factors, were the main predictors of oral targeted therapy adherence and persistence. Adherence to oral targeted therapies appears to be similar for patients on QD and BID regimens in the real-world setting.